The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5222/tmcd.2018.060
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of HBsAg levels in chronically infected patients with hepatitis B virus

Abstract: Kronik hepatit B (KHB) enfeksiyonunun tanı ve izlenmesinde serum HBV DNA düzeyi virus replikasyonunun en yaygın göstergesi olup, serolojik belirteçler ve alanin aminotransferaz (ALT) düzeyinin ölçümü ile birlikte yaygınlıkla kullanılmaktadır. Son yıllarda ise, kantitatif HBsAg düzeyleri ile HBV DNA ve ALT düzeylerinin ilişkili olduğu gösterilmiştir. Bu çalışmada, KHB hastalarında kantitatif HBsAg seviyelerinin HBV DNA, ALT-AST seviyeleri ve HBeAg ile karşılaştırılarak incelenmesi amaçlanmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In a limited number of population studies, it has been shown that qHBsAg measurement correlates with HBV DNA and may be a suitable marker for monitoring the effectiveness of HBV treatment [16] .Studies with a larger number of patients, it has been shown that the qHBsAg level could be used to differentiate inactive and active hepatitis B patientsandsince the use of qHBsAg tests are less costly in laboratories where molecular tests cannot be applied, it has been suggested as a more appropriate approach in CHB treatment monitoring [17,18] . In the present study, a negative correlation was determined between qHBsAg and HBV DNA levels and a significant positive correlation between HBeAg positivity and qHBsAg level.…”
Section: Discussionmentioning
confidence: 99%
“…In a limited number of population studies, it has been shown that qHBsAg measurement correlates with HBV DNA and may be a suitable marker for monitoring the effectiveness of HBV treatment [16] .Studies with a larger number of patients, it has been shown that the qHBsAg level could be used to differentiate inactive and active hepatitis B patientsandsince the use of qHBsAg tests are less costly in laboratories where molecular tests cannot be applied, it has been suggested as a more appropriate approach in CHB treatment monitoring [17,18] . In the present study, a negative correlation was determined between qHBsAg and HBV DNA levels and a significant positive correlation between HBeAg positivity and qHBsAg level.…”
Section: Discussionmentioning
confidence: 99%